Improved analysis of propylene oxide, propylene chlorohydrin and propylene bromohydrin - Hall, Wiley A.; Walse, Spencer S.; Jimenez, Leonel (Julius-Kühn-Archiv, 2018)
The benefits and deficiencies of several methods of analysis for PPO and PXH, including the aqueous extraction used in ASTA method 23.1 and the MTBE extraction method previously reported by the authors, will be discussed. Novel methods utilizing dynamic headspace extraction and solid phase microextraction (SPME) will also be reported with particular emphasis on preventing artefactual effects. Preliminary experiments have found that dynamic headspace sampling can lower detection limits by up to 3 orders of magnitude.